2015
DOI: 10.2190/pm.49.1.c
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Neuroleptic Malignant Syndrome in Patients Treated with Aripiprazole and Clozapine: A Case-Series Study and Short Review

Abstract: Our cases highlight the atypical features of NMS in patients being treated with combined ari-piprazole and clozapine. Consciousness change, modest elevation of creatine kinase, and leukocytosis were the most consistent findings; hyperthermia accounts for only some of the cases. This is a reminder of the importance of earlier detection of the soft signs and atypical features of NMS under this combined treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 28 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Several case reports and case series have accumulated on the occurrence of NMS in patients receiving aripiprazole. 26 , 27 Rigidity and altered mental state seem to be present frequently in such patients, while fever, diaphoresis and tachypnoea are less frequent. NMS has been reported to occur more commonly with fast upward titration of dosages of aripiprazole.…”
Section: Reports Of Atypical Antipsychotics Causing Nmsmentioning
confidence: 98%
See 1 more Smart Citation
“…Several case reports and case series have accumulated on the occurrence of NMS in patients receiving aripiprazole. 26 , 27 Rigidity and altered mental state seem to be present frequently in such patients, while fever, diaphoresis and tachypnoea are less frequent. NMS has been reported to occur more commonly with fast upward titration of dosages of aripiprazole.…”
Section: Reports Of Atypical Antipsychotics Causing Nmsmentioning
confidence: 98%
“…Aripiprazole has also been implicated in combination antipsychotic regimens, when used alongside other atypical antipsychotics such as clozapine. 27 …”
Section: Reports Of Atypical Antipsychotics Causing Nmsmentioning
confidence: 99%
“…Previous cases of NMS occurring in patients on dual aripiprazole and clozapine therapy report consciousness change and only modest elevation of CK, with hyperthermia not typically seen 8 …”
Section: Discussionmentioning
confidence: 84%
“…The pathophysiological mechanisms of NMS and catatonia remain unclear. However, it is hypothesized that abrupt and extensive D2 dopaminergic blockade of the anterior hypothalamus, corpus stratum, and basal ganglia corresponds to the clinical features of NMS, such as high fever, muscle rigidity, and an altered mental status, respectively ( 10 - 13 ). Additionally, a systematic review of NMS ( 14 ) reported that non-dopaminergic receptors, including serotonergic, adrenergic, and cholinergic receptors, may play an important role in the pathophysiology of NMS in extrapyramidal motor functions ( 15 ), thermoregulation, muscle metabolism ( 16 ), and mental status ( 17 ).…”
Section: Discussionmentioning
confidence: 99%